Biosemiotic Foundations of a Darwinian Approach to Cultural Evolution - Herrmann-Pillath Carsten (Cultural Science)
The present paper reflects on the state of evolutionary approaches to culture, which are mostly seen as essential for defining ‘cultural science’. They manifest two flaws that still block a productive synthesis between the sciences and the humanities. First, they employ an inflationary generic concept of culture that covers all information that is stored and transmitted non-genetically; this differs from the narrower uses in the humanities that focus on the diversity of cultures and their interactions. Second, they approach culture as observable and measurable ‘traits’, hence do not develop a precise concept of cultural meaning, which must take account of the fundamental property of reflexivity in human cognition. I propose an alternative view that is grounded in biosemiotic analysis of the brain, and that I relate to Robert Aunger’s conception of ‘neuromemetics’. I already contributed this idea to the first-stage debates about cultural science after 2008. The current paper adds much analytical detail on the systemic nature of cultural semiosis operating in a selectionist logic of brain dynamics, as theorized early on by F. A. von Hayek. I suggest that the bridge between the sciences and the humanities must be built via new disciplines in the neurosciences, such as cultural neuroscience, which avoids both biological reductionism and a mere analogical deployment of evolutionary diffusion analysis in the new field of cultural science. Semiotics is the overarching paradigm of integration, in the distinct versions of both biosemiotics and physiosemiotics. I suggest combining Peircean biosemiotics with Lotman’s concept of the ‘semiosphere’. In this context, culture is defined by reflexive operations that occur over internal boundaries of the semiosphere that are constitutive of the identity of the agent as the physical locus of neuromeme evolution.